KUALITAS SEMEN SEGAR DAN RECOVERY RATE (RR) SAPI LIMOUSIN PADA MUSIM YANG BERBEDA - Siti Sunami; Nurul Isnaini; Sri Wahjuningsih (TERNAK TROPIKA Journal of Tropical Animal Production, 2017)
This research aimed to determine the quality of fresh semen and recovery rate (RR) Limousin bulls at different seasons in Indonesia. The research materials were used semen sample and recording of 10 Limousin bulls on November 2015 until September 2016. The analyze was used by descriptive, while seasonal factors were determined by rainfall, they were divided into 2 stage (summer and rainy). The result was showed that the average of individual motility (60±0.07 %) on summer and (57.7±0.09 %) on rainy, Consentration of spermatozoa (1043±208 million/ml) on summer and (1013±175 million/ml) on rainy, post thawing motility (44±0.02 %) on summer and (41±0.05 %) on rainy, RR value (65±0.05 %) on summer and (55±0.09 %) on rainy, the production of frozen semen (1979±644.2 straw) on summer and (1623±379 straw) on rainy. It was concluded that the best quality of fresh until frozen semen was generally on summer with low rainfall. The seasonal effect for quality of semen Limousin bulls were individual motility, concentration, PTM, and RR value will be impacted for frozen semen produce. It was advisable to rejected the Limousin bulls with poor semen quality.Keywords: Seasonality, Summer, Rainy, Quality of Semen